To simplify the expression \( 4t + (-9t) \), you can combine the like terms:
\[ 4t - 9t = (4 - 9)t = -5t \]
Thus, the simplified expression is:
\[ -5t \]
4t+–9t
11 answers
To simplify the expression \( 4t + (-9t) \), you can combine the like terms:
\[ 4t - 9t = (4 - 9)t = -5t \]
Thus, the simplified expression is:
\[ -5t \]
To simplify the expression \( 2x + 5 - 2 + 5 - 4 - 2x \), we can first combine like terms:
Combine the \( x \) terms: \[ 2x - 2x = 0 \]
Now combine the constant terms: \[ 5 - 2 + 5 - 4 = 4 \]
So, when we combine everything, we have: \[ 0 + 4 = 4 \]
Thus, the simplified expression is: \[ 4 \]
To simplify the expression \( 3w + 7w + 8 + 9w + 9w + w \), we combine the like terms.
Combine the \( w \) terms: \[ 3w + 7w + 9w + 9w + w = (3 + 7 + 9 + 9 + 1)w = 29w \]
The constant term is \( 8 \).
So, the simplified expression is: \[ 29w + 8 \]
To simplify the expression \( 6j + (-9j) + (-9) + (-7) + (-5j) \), we will combine like terms.
Combine the \( j \) terms: \[ 6j - 9j - 5j = (6 - 9 - 5)j = (-8)j = -8j \]
Combine the constant terms: \[ -9 - 7 = -16 \]
Putting it all together, we have: \[ -8j - 16 \]
Thus, the simplified expression is: \[ -8j - 16 \]
To simplify the expression \( 5x + 8x + 8x + 8x + 3x \), we combine the like terms:
So, the simplified expression is: \[ 32x \]
To simplify the expression \( 8y + 9 + 3y + 7 + 6y + 5y \), we'll combine the like terms.
Combine the \( y \) terms: \[ 8y + 3y + 6y + 5y = (8 + 3 + 6 + 5)y = 22y \]
Combine the constant terms: \[ 9 + 7 = 16 \]
Putting it all together, we have: \[ 22y + 16 \]
Thus, the simplified expression is: \[ 22y + 16 \]